2019
DOI: 10.1001/jamaoto.2019.1437
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction Patterns During Drug-Induced Sleep Endoscopy vs Natural Sleep Endoscopy in Patients With Obstructive Sleep Apnea

Abstract: IMPORTANCE Drug-induced sleep endoscopy (DISE) has been suggested to be a valuable technique for identifying the obstruction site associated with sleep-disordered breathing. However, the reliability of DISE findings is controversial because the procedure uses sedative drugs, which may have implications for the obstruction patterns observed on DISE. OBJECTIVE To compare the obstruction patterns during DISE with the obstruction patterns during natural sleep endoscopy (NSE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…However, previous research has indicated that collapse patterns of the upper airway appeared to be in agreement between DISE and natural sleep endoscopy. It seems therefore that DISE is a relatively reliable exam [ 29 ]. Third, the diagnosis of positional dependency and the prescription of positional therapy are fundamentally based on PSG reports rather than DISE findings, although DISE could better elucidate the underlying anatomical dissimilarities between positional and non-positional OSA.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has indicated that collapse patterns of the upper airway appeared to be in agreement between DISE and natural sleep endoscopy. It seems therefore that DISE is a relatively reliable exam [ 29 ]. Third, the diagnosis of positional dependency and the prescription of positional therapy are fundamentally based on PSG reports rather than DISE findings, although DISE could better elucidate the underlying anatomical dissimilarities between positional and non-positional OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Even if DISE is compared to upper airway investigations performed during natural sleep, the DISE technique is a time and manpower saving approach. Park et al have recently compared the levels of agreement between a midazolam-based DISE approach and natural sleep endoscopy and found significant agreements regarding obstructions at the epiglottis (92.3%), the oropharynx lateral wall (88.5%), and the velum (76.9%) [23].…”
Section: Discussionmentioning
confidence: 99%
“…The following classifications currently include VOTE (velum, oropharynx, tongue base, epiglottis) classification and NOHL (nose, oropharynx, hypopharynx, larynx) classification. 1,4 In terms of these classification methods to observe the dynamic pattern of the oropharynx lateral wall, tongue base, and epiglottis, retrolingual obstruction can be identified.…”
Section: Introductionmentioning
confidence: 99%